Pattern of menstruation and its problem among adolescent girls: a school based cross-sectional study - Poudel, Pramila (International Journal of Contemporary Pediatrics, 2022)
Background: Menstruation is a normal physiological process that begins during puberty and continues throughout the 5th decade of woman’s life. The pattern of menstruation varies from woman to women. The aim of present study was to identify the pattern of menstruation and its problems among adolescent girls at Birgunj, Nepal. Methods: A quantitative, descriptive cross-sectional school-based study was conducted among 244 girls studying in grade 8, 9 and 10 using a semi structured self-administered questionnaire. The obtained data was analyzed using descriptive and inferential statistics using statistical package for the social sciences (SPSS) version 23. The probability value (p value) of <0.05 was considered statistically significant at 95% confidence level. Results: Result revealed that mean age of adolescent was 14.97±1.02 and mean age at menarche was 13.13±0.72 years. Almost half of the adolescents (48.3%) had moderate to severe pain during menstruation. Majority (78.27%) had regular pattern of menstruation. Nearly 1/10th (8.6%) of adolescents missed school during menstruation and the major cause of absenteeism was pain and discomfort (76.19%). Majority (81.6%) had restrictions in religious/family activities and (76.8%) had feeling of tiredness during menstruation. The regularity of menstruation and dysmenorrhea was significantly associated with age of adolescents at the level of p value 0.05. Conclusions: Various physical and social problems are experienced by the adolescent during menstruation. These problems have impact on the lifestyle of the adolescents including missed school days. Social restrictions during menstruation may lead to various psychological impacts on adolescents. Education regarding hygiene, self-care and management of menstrual symptoms, clarifying menstrual taboos among family and community members is required so that the adolescent can experience their feminine feature with health and dignity.